BURIED BUMPER SYNDROME - Hafeez, Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Percutaneous Endoscopic Gastrostomy (PEG) is a procedure in which a tube is placed in the stomach through abdominal wall with the help of flexible upper Gastrointestinal Endoscope. This procedure is done for nutrition in patients who are unable to swallow e.g., in neurodegenerative disorder, brain injury or stroke etc. Side effects include wound infection, peristomal leakage, transient gastroparesis and bleeding. Another complication is Buried Bumper Syndrome that develops when external cushion is kept in tight opposition with abdominal wall, the internal bumper erodes the gastric mucosa and buried in the wall.1 It is confirmed with upper gastrointestinal endoscopy. Its treatment is removal of the tube. In our case, PEG tube was placed in a young man with persistent vegetative state for feeding. After a month tube blocked, on Upper Gastro endoscopy PEG tube head was found buried in stomach wall (Buried Bumper Syndrome). PEG Tube was removed and replaced with PEG replacement tube that re-established feeding.